2018
DOI: 10.18203/2349-2902.isj20181421
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of impact of social factor in pediatric trauma at teaching hospital of Vindhya region of India

Abstract: Background: Pediatric trauma i.e. Fall, RTA, burn and other type of trauma is primarily seen in neglected young children, these children’s are unattended to and unprotected at home due to overburdened parents in nuclear family busy with various household and outdoor jobs. In present study aims to analyse the different aspect of social factors that related to trauma in pediatric age group.Methods: The present retrospective study was carried out in 367 patients of the age group <1-15 years during the period 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…After the age of one, children walk, which allows them to discover the world around them, play outside, and more easily escape the supervision of their parents. 11 We also found out the percentage of injuries that had taken place during the weekends (28.1 %) in relation to weekdays (71.8 %) which is in accordant with an analysis study done in Morocco. 12 In opposition to this a study conducted in Karachi mentions weekends bearing more reported cases.…”
Section: Discussionsupporting
confidence: 88%
“…After the age of one, children walk, which allows them to discover the world around them, play outside, and more easily escape the supervision of their parents. 11 We also found out the percentage of injuries that had taken place during the weekends (28.1 %) in relation to weekdays (71.8 %) which is in accordant with an analysis study done in Morocco. 12 In opposition to this a study conducted in Karachi mentions weekends bearing more reported cases.…”
Section: Discussionsupporting
confidence: 88%